2021
DOI: 10.3389/fmicb.2021.787283
|View full text |Cite
|
Sign up to set email alerts
|

Global Characterization of Fungal Mitogenomes: New Insights on Genomic Diversity and Dynamism of Coding Genes and Accessory Elements

Abstract: Fungi comprise a great diversity of species with distinct ecological functions and lifestyles. Similar to other eukaryotes, fungi rely on interactions with prokaryotes and one of the most important symbiotic events was the acquisition of mitochondria. Mitochondria are organelles found in eukaryotic cells whose main function is to generate energy through aerobic respiration. Mitogenomes (mtDNAs) are double-stranded circular or linear DNA from mitochondria that may contain core genes and accessory elements that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 95 publications
1
28
3
Order By: Relevance
“…All complete mitogenomes in Saccharomycetaceae encode eight protein genes, seven respiratory-chain protein genes ( atp6 , atp8 , atp9 , cob , cox1 , cox2 , and cox3 ) and one ribosomal protein gene var1 , SSU and LSU rRNAs, and 22–24 tRNAs. This is in contrast with a recent report that “no gene is universally conserved in fungal mitogenomes” ( Fonseca et al, 2021 ). Although it is inevitable that fewer mitochondrial genes are shared when more diverse lineages are included ( Roger et al, 2017 ), the variation of mitogenome sequence quality could have been an important reason for the discrepancy on gene conservation among yeast mitogenomes.…”
Section: Stable Gene Content In Yeast Mitogenomescontrasting
confidence: 99%
See 1 more Smart Citation
“…All complete mitogenomes in Saccharomycetaceae encode eight protein genes, seven respiratory-chain protein genes ( atp6 , atp8 , atp9 , cob , cox1 , cox2 , and cox3 ) and one ribosomal protein gene var1 , SSU and LSU rRNAs, and 22–24 tRNAs. This is in contrast with a recent report that “no gene is universally conserved in fungal mitogenomes” ( Fonseca et al, 2021 ). Although it is inevitable that fewer mitochondrial genes are shared when more diverse lineages are included ( Roger et al, 2017 ), the variation of mitogenome sequence quality could have been an important reason for the discrepancy on gene conservation among yeast mitogenomes.…”
Section: Stable Gene Content In Yeast Mitogenomescontrasting
confidence: 99%
“…Although it is inevitable that fewer mitochondrial genes are shared when more diverse lineages are included ( Roger et al, 2017 ), the variation of mitogenome sequence quality could have been an important reason for the discrepancy on gene conservation among yeast mitogenomes. For instance, the two S. cerevisiae mitogenomes (accessions: CM002421 and CP046458 ) reportedly missing atp6 by Fonseca et al (2021) are 22,149 bp (including 13,247 Ns for gaps) and 49,451 bp (517 Ns) in length, respectively, much shorter than the average 82.5 Kb [ranging from 74.2 to 92.2 kb in Xiao et al (2017) ] of S. cerevisiae mitogenomes ( Figure 1 ). The Saccharomycodaceae family has a sole case of gene loss involving a protein gene.…”
Section: Stable Gene Content In Yeast Mitogenomesmentioning
confidence: 99%
“…Rpo-based phylogeny revealed both phyla-specific clades and rpo sequences that are shared between species of different phyla. This diversity of rpo sequences observed in the literature suggests a possible horizontal gene transfer between fungal species [ 203 , 204 , 205 ]. The mitochondrial codon usage for the AB species is similar to that reported for other ascomycete fungi [ 187 ].…”
Section: Discussionmentioning
confidence: 89%
“…Previous research found that rpo was only found in species belonging to the fungal phyla Ascomycota, Basidiomycota and Chytridiomycota. Although rpo homologs were found in both Ascomycota and Basidiomycota fungal species, this was only in 10% of the Ascomycota species (227) sampled, compared to 57% for Basidiomycota (116) [ 203 ]. This means that P. koolunga is among a small percentage of species within the Ascomycota phylum that harbours an rpo homolog.…”
Section: Discussionmentioning
confidence: 99%
“…Fungal mitochondrial genomes are typically small, circular and double-stranded DNA molecules, with a typical set of mitochondrial genes with identical gene order. Extensive mitochondrial genome comparisons within the fungal kingdom have shown that any gene has a mitochondrial localization in all fungal species [13], suggesting that the use of mitochondrial gene diversity cannot be applied as a universal marker for fungi. Nonetheless, the analysis of mitochondrial diversity can be successfully applied to differentiate species within orders [14] or species [15,16].…”
Section: Introductionmentioning
confidence: 99%